Influence of perceived risks in farmer’s decision towards sustainable farm practices, Evidence from Northern Thailand - Llones, C.; Suwanmaneepong, S. (International Journal of Agricultural Technology, 2021)
Under the sustainable development goals, nations worldwide are enjoined to take immediate action through sustainable adaptations to mitigate climate variability and change. At the same time, agriculture is both a victim and a contributor to climate change. The situation prompted Thailand’s agriculture to explore sustainable practices for food security and deliver environmental services. Using a binary logit model, the potential effects of farmers’ perceived risks on adopting sustainable farming practices were investigated. The study revealed that farmers are somewhat hesitant to radically shift from their usual practices due to associated costs and the perceived potential risks. In addition, the study found that factors affecting adoption were site-specific. Hence, government actions should be flexible and tailored to a local level while still aligning with the national policy goals. For this, inter-agency coordination at the local, provincial and central levels is needed for agricultural support and enable farmers to make necessary changes to successfully adapt to emerging risks